2016
DOI: 10.1590/1516-3180.2016.0111300616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of knee arthroplasty in the state of São Paulo between 2003 and 2010

Abstract: CONTEXT AND OBJECTIVE: The volume of knee arthroplasty procedures has increased over the last decade. The aim of this study was to estimate the frequency of these procedures performed within the public healthcare system of the state of São Paulo between 2003 and 2010. DESIGN AND SETTING: Cross-sectional study conducted in the state of São Paulo by researchers at Hospital do Servidor Público do Estado de São Paulo. METHODS: A sample of 10,952 patients (7,891 females and 3,061 males) who underwent primary total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Online supplemental figure 1 illustrates the selection process. Online supplemental tables 2 and 3 describe the excluded registry and non-registry periods reports 3 9 10 19–29 Tables 1 and 2. present the included non-registry and registry periods data, respectively, after eligibility check.…”
Section: Resultsmentioning
confidence: 99%
“…Online supplemental figure 1 illustrates the selection process. Online supplemental tables 2 and 3 describe the excluded registry and non-registry periods reports 3 9 10 19–29 Tables 1 and 2. present the included non-registry and registry periods data, respectively, after eligibility check.…”
Section: Resultsmentioning
confidence: 99%
“…9 The constant decline in age-adjusted mortality rates for all causes including chronic diseases, combined with the increasing size of the elderly population, is bringing up a new agenda for medical and public health research. 10 This agenda relates not only to avoidance of lethal diseases, but also to reduction of discomfort and painful conditions.…”
Section: Faculdade De Medicina Da Universidade De São Paulo (Fmusp) mentioning
confidence: 99%
“…The aging of the Brazilian population, as a result of increased life expectancy, contributes to the increase of the arthroplasties at a national level. [1][2][3] Several studies have demonstrated that this increase reflects a worldwide trend. Other places, such as the United Kingdom and Australia, saw an increase in the number of arthroplasties during the same period, even though life expectancy there is greater than in Brasil.…”
mentioning
confidence: 99%
“…Other places, such as the United Kingdom and Australia, saw an increase in the number of arthroplasties during the same period, even though life expectancy there is greater than in Brasil. [2][3][4][5] Over 76 years, from 1940 to 2016, the life expectancy of the Brazilians at birth increased in more than 30 years and today is 75.8 years, an increase of 3 months and 11 days compared to 2015, according to the Brazilian Institute of Geography and Statistics (IBGE). Data from the 2016 Mortality Table showed that, on average, women live longer than men.…”
mentioning
confidence: 99%